KOMITMEN ORGANISASI DALAM IMPLEMENTASI PROGRAM BPJS KETENAGAKERJAAN SEBAGAI BENTUK PERLINDUNGAN UNTUK MENINGKATKAN KESEJAHTERAAN KARYAWAN (Studi Pada BPJS Ketenagakerjaan Cabang Magelang) - Anisa, Ela; Siharis, Alkadri Kusalendra (Jurnal Kesejahteraan dan Pelayanan Sosial, 2020)
Companies that have an organizational commitment to implement the BPJS Employment Program which aims to provide basic protection to employees to overcome socio-economic risks through social insurance can improve employee performance because employees feel prosperous. The purpose of this study was to determine the types of BPJS employment programs and their effects on employee welfare. The research method used is a qualitative research method in the form of interviews with four employees from different companies who have implemented the BPJS employment program and observations at the BPJS Employment office. The results of this study indicate that companies must commit to implementing four BPJS employment programs, namely: Work Accident Insurance (JKK), Death Insurance (JKM), Old Age Insurance (JHT), Pension Insurance (JP) so that employees feel protected. The implementation of the BPJS Employment program can be said to be quite good, as seen from the increasing number of companies that receive BPJS wage employment in the Magelang branch office each year.Keywords: Organization Commitment, Employment BPJS, Employee Welfare